Effect of stocking density on survival and growth of post-settlement juveniles of aquaculture reared Mediterranean spider crab Maja squinado (Herbst, 1788) - Millot, Rémi; Debattice, Camille; Ligorini, Viviana; Bracconi, Jérémy; Gattacceca, Nicolas; Crescioni, Ambre; Ronchi-Perfetti, Jean-Baptiste; Vela, Alexandre; Bastien, Romain; Aiello, Antoine; Filippi, Jean-José (Frontiers in Aquaculture, 2025)
The Mediterranean spider crab, Maja squinado (Herbst, 1788), is one of the largest species of spider crab and holds significant interest for commercial and stock enhancement purposes. Thus, it is essential to identify optimal rearing conditions to attempt mass production, as several factors affect the growth and survival of this species during the early juvenile phase in aquaculture. In this study, we evaluated the effect of stocking density on the growth parameters and survival rate of M. squinado reared in an experimental hatchery as part of a spider crab stock enhancement feasibility project. Groups of spider crabs were reared at two initial densities (1.6 and 4.6 individuals·L−1). After 29 days of culture (i.e., from megalopae to C3 juveniles), early juveniles reared at the higher density showed a significantly higher weight gain ratio and specific growth rate as well as a significantly higher Fulton’s condition index specifically for C3 juveniles, reflecting a better general well-being. In contrast, the survival at the higher density was negatively affected compared to the lower rearing density. This study improves baseline knowledge about M. squinado rearing to help develop commercial applications and establish management strategies and restoration programs for endangered M. squinado populations going forward.